1996
DOI: 10.1080/02652039609374415
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin B1contamination in groundnut samples collected from different geographical regions of India: A multicentre study

Abstract: Under a multicentre study conducted by the Indian Council of Medical Research, 2062 samples of groundnut were collected from rural and urban areas of 11 states representing different geographical regions of the country. These samples were analysed for aflatoxin B1 using the AOAC method. Analytical quality assurance between various participating laboratories was ensured through analysis of check-samples. Twenty-one per cent of groundnut samples collected from 11 states exceeded the permissible Indian regulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 1 publication
0
8
0
1
Order By: Relevance
“…Various surveys conducted in different parts of India (Rati and Shanta 1994;Sharma et al 1994;Bhat et al 1996;Prashad et al 1997;Sinha et al 1999) have revealed groundnuts and groundnut products to be high-risk commodities for aflatoxin contamination.…”
Section: Introductionmentioning
confidence: 97%
“…Various surveys conducted in different parts of India (Rati and Shanta 1994;Sharma et al 1994;Bhat et al 1996;Prashad et al 1997;Sinha et al 1999) have revealed groundnuts and groundnut products to be high-risk commodities for aflatoxin contamination.…”
Section: Introductionmentioning
confidence: 97%
“…The mutation at codon 249 is very low or absent in parts of the world where exposure to dietary aflatoxin is low [28,29]. Dietary aflatoxin B1 levels vary greatly among Indian states [30,31]. Murugavel et al [32] detected aflatoxin B 1 in the liver biopsies of more than 50% of the HCCs cases in their study.…”
Section: Discussionmentioning
confidence: 96%
“…The government is aiming at reducing aflatoxin and PAH levels in copra and in crude coconut oil. However any scheme must provide a real financial incentive to cover the increased processing costs necessary for the production of dry, mould-free copra [7]. To reduce the potential incidence of aflatoxin B 1 contamination to 5% of samples it will be necessary to dry to average marker levels of 4.6, 8.8 and 5.3% for kukum, tapahan and sun-dried copra respectively [8].…”
Section: Philippine Regulatory Action In Foodmentioning
confidence: 99%